Characterization and Preparation of Ni/γAl2O3 Catalyst for Acetylation of Glycerol in a Fixed Bed Reactor Applied as an Octane Booster for Commercial Fuels - Dewajani, Heny; Chumaidi, Achmad; Suryandari, Ade Sonya; Dewi, Ernia Novika; Ahsan, Muhammad Hafizh (Universitas Negeri Semarang, 2021)
Glycerol is a by-product of biodiesel production with the amount of 10% of the total biodiesel product. To increase the utility and economic value of glycerol, it can be processed into several derivative products. One of the glycerol derivative products is currently being developed through the acetylation process. Glycerol acetylation product has been investigated as a component that can be used to increase the octane number of commercial fuels, otherwise known as bio-additives or octane boosters. This study aims to convert glycerol from the by-product of biodiesel production through the acetylation process using a modified solid catalyst Ni/γ-Al2O3 in a fixed bed reactor. The focus of this research is to study the effect of reactant flow rate and the mole ratio of glycerol to acetic acid on glycerol conversion. The variations used were flow rates of feed from 40, 60, 80 and 100 ml/minute, and the mole ratio of glycerol to acetic acid was 1:3, 1:5, 1:7, and 1:9. The experiment was carried out in several stages, namely: preparation and modification of the catalyst, the acetylation process and product application into commercial fuels. The acetylation reaction took place at a temperature of 100 °C and the mass of the catalyst used was 5% of the mass of glycerol. The results showed that the highest conversion of 74.24% was achieved under operating conditions with a reactant flow rate of 40 ml/min and glycerol to acetic acid mole ratio of 1:9. The utilization of acetylation products as bio-additives is carried out by adding reaction products to Pertamax fuel. The highest increase in octane number of Pertamax fuel at the addition of 8% volume of acetylation product from the initial octane number of 93 increased to 102 (increased by 10%).